Tall Zirāʿa, Jordanien: Die Kalksteingefäße aus der frührömischen Zeit – Religiöse uns sozio-öknomische Implikationen - Häser, Jutta; Vieweger, Dieter (e-Forschungsberichte des DAI, 2023)
Chalk vessels of specific types have been recognized as religious markers for a Jewish presence. They have been used in the daily purification rites and are well known from Jewish sites in lsrael/Palestine. They can be dated from 30 BC to araund 100 AD. Only few specimens are known from Transjordan. However, 81 pieces were excavated from Area I and II on Tall Zirāʿa in Northwest Jordan. This Ieads to the assumption that this site was at least partly inhabited by a Jewish population.